Cues to deception in Islamic websites text-based content and design: a systematic literature review - Ahmed Mohamed, Fatima; Sheikh Abdul Aziz, Madihah; Zulkifli, Zahidah (IIUM Press, 2021)
Deception in the virtual environment is rapidly growing, especially with Islamic websites (I-web). This paper presents the current evidence relative to the investigation of cues to deception in Islamic websites text-based content and design. To meet the objective of this study, a systematic literature review (SLR) has been applied. The findings from the systematic literature review (SLR), includes a set of 12 primary studies out of 625 extracted papers and a total of 15 cues that have as well been acknowledged. The cues were divided into two components, text-based content and design. Of which, nine text-based content cues were identified, equivalent to 60% of the overall cues, and another 6 cues (40%) were on design. Majority of the text-based cues were related to the use of fake and weak Hadith, while the design cues were more related to the uncertain appearance and poor design of the Islamic websites. The findings of this study may serve the users, content providers and websites designers on the possible cues that constitute deception in the Islamic websites, textual content and design. The cues may guide users in selecting the right information, which are reliable, credible, and valid, particularly in the context of Islamic knowledge and teaching